Chronic arthritis induced in rats by cell wall fragments of Eubacterium species from the human intestinal flora. - Severijnen, A J (1990)
To investigate arthritis-inducing properties of Eubacterium species, which are major residents of the human intestinal flora, cell wall fragments (CWF) of several Eubacterium strains were prepared and tested in an animal model. After a single intraperitoneal injection in the rat, CWF of E. aerofaciens, E. contortum, and E. lentum induced a chronic polyarthritis. E. limosum and E. tortuosum CWF induced an acute self-limiting joint inflammation, whereas E. rectale CWF failed to do so. The rhamnose contents of the isolated CWF were not related to their arthritis-inducing properties. Paradoxically, the sensitivity of CWF to lysozyme digestion, which is regarded as a parameter for the clearance of CWF in tissues, appeared to be positively correlated with the ability of Eubacterium CWF to induce chronic joint inflammation. Our findings show the diversity in arthritis-inducing properties among different species of the anaerobic genus Eubacterium and underline the importance of the anaerobic intestinal flora in the induction of joint inflammation.